Process governance and administration of in-service education in the national education system - Marwan Marwan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The purpose of this research is to critically examine the consistency and inconsistency of laws and regulations regarding the administration of higher education in positions within the national education system. It identifies the input, process and output mechanisms of higher education in positions within the national education system with laws and regulations on the national education system. organize higher education in the national education system. The research was conducted at in-service universities. Data collection is done through literature study (normative law) and field research (empirical law). Normative legal research leads to descriptions in the form of exposure, comparison, and interpretation of applicable law or positive law, while empirical legal research (sociological law) was conducted through observation and in-depth interviews with competent sources related to the problem being studied (objects). studied) to obtain primary data. The data were analyzed qualitatively which was empirical (inductive) by conducting interviews, observations and documentation and combining primary and secondary data (deductive). The results of the study indicate several things including the input, process and output mechanisms which are a necessity in the higher education management function, need to be improved by implementing standards, processes, and education. Internal and external regulations have an impact on the management and delivery of education. Graduates must have differences in quality and quantity (output, outcome), compared to other universities so that collaboration with professional institutions can be established. Juridical, sociological, and philosophical governance in higher education in positions within a State Higher Education (PTN) system is a reform in higher education.